2009
DOI: 10.1128/mcb.00980-08
|View full text |Cite|
|
Sign up to set email alerts
|

The TSC-mTOR Pathway Mediates Translational Activation of TOP mRNAs by Insulin Largely in a Raptor- or Rictor-Independent Manner

Abstract: The stimulatory effect of insulin on protein synthesis is due to its ability to activate various translation factors. We now show that insulin can increase protein synthesis capacity also by translational activation of TOP mRNAs encoding various components of the translation machinery. This translational activation involves the tuberous sclerosis complex (TSC), as the knockout of TSC1 or TSC2 rescues TOP mRNAs from translational repression in mitotically arrested cells. Similar results were obtained upon overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 62 publications
5
77
0
Order By: Relevance
“…Although both S6K and 4E-BP initiate translation in response to mTOR activation, they seem to act on specific mRNA populations. Although this view has been challenged recently [34], S6K is thought to specifically favour the translation of mRNA species containing an oligopyrimidine tract at the 5′ terminus (TOP-mRNAs), such as those encoding ribosomal proteins or elongation factors. The phosphorylation and dissociation of 4E-BP from eukaryotic translation initiation factor 4E (eIF-4E) allows the translation of cap-containing mRNAs and of mRNAs with 5′ secondary structures, which frequently encode proteins involved in proliferation [35].…”
Section: Discussionmentioning
confidence: 99%
“…Although both S6K and 4E-BP initiate translation in response to mTOR activation, they seem to act on specific mRNA populations. Although this view has been challenged recently [34], S6K is thought to specifically favour the translation of mRNA species containing an oligopyrimidine tract at the 5′ terminus (TOP-mRNAs), such as those encoding ribosomal proteins or elongation factors. The phosphorylation and dissociation of 4E-BP from eukaryotic translation initiation factor 4E (eIF-4E) allows the translation of cap-containing mRNAs and of mRNAs with 5′ secondary structures, which frequently encode proteins involved in proliferation [35].…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggested that mTOR functions in adult skeletal muscle require only mTORC1 (Bentzinger et al, 2008). However, there is evidence that some functions of mTOR, such as the activation of terminal oligopyrimidine mRNA translation, could be independent of mTORC1 and mTORC2 (Patursky-Polischuk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the event of stresses, such as amino acid starvation, TOP mRNAs are selectively repressed at the level of translation. 45,46 The upstream regulatory pathways regulating TOP translation involves the phosphatidylinositol 3-kinase (PI3K) and mTOR pathways, 47,48 and several RNA-binding proteins have been proposed to regulate the translation of TOP mRNAs. [49][50][51] However, the exact mechanism and wiring of upstream pathways is still largely unresolved.…”
Section: Mir-10 On Topmentioning
confidence: 99%